Green fabrication of copper nanopeprintss dispersed in walnut oil using laser ablation technique - Sadrolhosseini, Amir Reza (Hindawi Publishing Corporation, 2016)
Synthesis of copper nanoparticles was achieved by laser irradiation of copper plate in walnut oil. The copper plate was irradiated using Nd:YAG pulse laser at different ablation time from 5 to 50 minutes, and the prepared samples were characterized using analytical methods to find the optical absorption, morphology, particle size, and capping of copper nanoparticles with walnut oil. Consequently, the absorption peak appeared at about 615, 606, 588, 576, and 561 nm; and the nanoparticles formed in spherical shape in walnut oil. The particle size varied from 25 to 4.01 nm, and the tail of the carbonyl band capped the copper nanoparticles through the electron transfer from the carboxylic group to copper nanoparticles. The refractive indices of the nanofluid were measured using a surface plasmon resonance technique and changed from 1.4691 + 0.008i to 1.4682 + 0.043i as the volume fraction increased from 0.0257 × 10−5 to 1.26 × 10−5. Consequently, the laser ablation method is environmentally sensitive (i.e., green) and thus is suitable for the fabrication of copper nanoparticles in walnut oil without any agent.